Nilai Perusahaan Ditinjau dari Pengaruh Kebijakan Dividen, Keputusan Investasi dan Keputusan Pendanaan - Taufik Hidayat; Ayang Mulyana; Senop Permadi (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2023)
The value of a company is the goal that the company aims to achieve as a result of its success and reputation built over the years. The company's primary focus is to achieve maximum profitability and maintain a high value. Additionally, by optimizing the company's value, it becomes a consideration for prospective investors in making investment decisions. This research aims to examine the influence of dividend policy, investment decisions, and financing decisions on the value of food and beverage companies listed on the Indonesia Stock Exchange. Purposive sampling was used as the sampling method. Panel data regression analysis was employed to analyze the data. The results of the analysis indicate that, partially, dividend policy has an impact on the value of the company, while investment decisions and financing decisions do not affect the value of the company. Simultaneously, dividend policy, investment decisions, and financing decisions collectively influence the value of the company